How to succeed in dermatologic surgery - A. Wysong; E. McBurney (Wolters Kluwer, 2019)
This article explores the many facets of success within dermatologic surgery. We incorporate advice from both dermatologists and dermatologic surgeons to provide overall advice and strategies for success. In addition, we discuss specific tips for matching and career development.